A versatile binder-free TiO2 paste for dye-sensitized solar cells1. Issue 37 (25th April 2015) - Yune, Jeremy H.; Karatchevtseva, Inna; Evans, Peter J.; Wagner, Klaudia; Griffith, Matthew J.; Officer, David; Triani, Gerry
<x xml:space="preserve">Abstract</x> In this study, binder-free TiO2 colloidal pastes have been prepared using a variety of heterocyclic bases with diverse characteristics to produce robust photoanodes for dye-sensitized solar cells (DSSC) from a single cast film thickness of 5 micron.